Analysis of Bank Health Before and After the Implementation of Pernyataan Standar Akuntansi Keuangan (PSAK) 71 - Antari, Wulan Dwi; Anggraini, Triana; Rosita*, Reni (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2022)
The change in the implementation of PSAK 55 to PSAK 71 at the beginning of 2020 is an important event that has occurred in the banking industry, with this research aims to see whether there are differences in the soundness of banks before and after the application of PSAK 71 to Conventional Banks listed in the Indonesia Stock Exchange (IDX) in 2019-2020. Taking the sample of 31 banks was selected through purposive sampling. Using a non-parametric test namely, the Wilcoxon rank sign range test, assessed by the SPSS v.22. Bank soundness level is measured using Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC). Research gives the result that the level of bank soundness has an overall difference before and after the application of PSAK 71. Keywords: Bank soundness; PSAK 71; Conventional Banks; Indonesia Stock Exchange (IDX); RGEC Pergantian pemberlakuan PSAK 55 menjadi PSAK 71 pada awal tahun 2020 menjadi peristiwa penting yang terjadi pada industri perbankan, dengan ini penelitian bertujuan untuk melihat adakah perbedaan tingkat kesehatan bank sebelum dan sesudah penerapan PSAK 71 pada Bank Konvensional yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2019 – 2020. Sampel sebanyak 31 Bank dengan teknik pengambilan sampel purposive sampling. Menggunakan uji non-parametrik yaitu uji wilcoxon sign rank test. Pengukuran tingkat kesehatan bank menggunakan Risk Profile, Good Corporate Governance, Earnings, dan Capital (RGEC). Penelitian memberikan hasil bahwa tingkat kesehatan bank memiliki perbedaan secara menyeluruh ketika sebelum dan sesudah penerapan PSAK 71. Kata Kunci: Kesehatan Bank; PSAK 71; Bank Konvensional; Bursa Efek Indonesia (BEI); RGEC